PENGARUH PENERAPAN TEKNIK DUA TINGGAL DUA TAMU TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 27 - Hajriati, Teti; Rismen, Sefna; Febriana, Rina (STKIP PGRI Sumbar, 2014)
ABSTRACTThe background of this research by the student in learning individually andstudenâs comprehension mathematical concept still low at the seventh grade of SMPN 27 Padang.. This research is an experiment research, with random research designon the subject. Researchâs population is all of student at the seventh grade of SMPN 27 Padang who registerin academic year 2013/2014. Researchâs sample is class VII.1 as an experiment class, and VII.2 as a control class, researchâs instrument isan essay test, with reliabilitas test r11 is 0,87. hypothesis result is P-value = 0,003, it means that is smaller than Â so hypothesis on this research is accepted. The conclusion that studentâs comprehension mathematical that uses Two Stay Two Stray Technique is better than convensional learning by the student at the seventh grade of SMPN 27 Padang.